Neonatal Cholestasis Progressing to a Multisystem Syndrome With Liver Cirrhosis in Two Siblings With FARSA Deficiency: An Evolving Hepatological Phenotype - Y. Aelvoet; P. Verloo; A. Vanlander; S. Vande Velde; S. Van Biervliet; P. De Bruyne; L. Hoste; A. Dheedene; L. Pottie; A. Hoorens; M. Mendes; R. De Bruyne (JIMD Reports)
ABSTRACT Biallelic variants in FARSA or FARSB are associated with reduced cytoplasmic phenylalanyl‐tRNA synthetase (FARS1) activity and underlie a multisystem syndrome characterized by growth limitation, developmental delay, brain calcifications, interstitial lung disease (ILD), and liver involvement. ILD is an early characteristic feature marked by bilateral ground‐glass opacification, subpleural cysts, and cholesterol pneumonitis and seems to be the leading cause of disease burden and death. A 7‐year‐old Iraqi girl was referred with idiopathic liver disease. Her previous medical history revealed neonatal jaundice, failure to thrive (FTT), mild motor development delay, and variceal bleeding at the age of 6 years in Iraq. She was diagnosed with liver cirrhosis, severe splenomegaly, profound thrombocytopenia, and hypoalbuminemia. Her younger brother presented to our hospital at the age of 2 months with neonatal cholestasis progressing to hepatic failure with impaired synthetic function. He suffered from coagulopathy, intractable hypoalbuminemia, FTT with axial hypotonia, multiple infectious episodes, and a prothrombotic state. Whole exome sequencing revealed compound heterozygous missense variants p.(Pro226Leu) and p.(Arg475Trp) in FARSA (OMIM: 602918) in both siblings. Even in the absence of overt clinical symptoms, chest computer tomography following diagnosis showed ILD in both siblings. Decreased FARS1 activity was measured in fibroblasts of both patients. We are the first to report on two siblings with neonatal jaundice evolving to severe liver disease as a cardinal symptom of cytosolic FARS deficiency. We emphasize the importance of performing a pulmonary workup in the diagnostic process of liver failure of unknown origin for detection of ILD as a clue to diagnosis.